Türkiye’ de faiz oranını etkileyen faktörler ve faiz oranlarının düşürülmesi için alınması gereken önlemler - Çelen, Durmuş (My University, 2000)
FACTORS THAT AFFECT THE INTEREST RATE IN TURKEY AND MEASURES THAT ARE TO BE MET IN ORDER TO DECREASE THE INTEREST RATES Notwithstanding the fact that the Turkish economy has realized certain steps, it can be told that it has not yet gained a sound and healthy structure and that it will be highly dependent on the outer world in the 21st century. Foreign capital is of great importance in terms of the added value it creates, especially for countries making efforts to develop economically. As stated above, due to the high acceleration of data flow speed, the whole world can always obtain the same information at the same time, thus the rational investors can monitor the investment possibilities in all economies. At this point, the interest rates are determinant for investment decisions. Therefore, estimation of changes in interest rates in the most appropriate manner in the future has become one of main targets of economic researches. After presentation of Turkey's economic overview in the introductory section, we can discuss the working method of our thesis. In Part One of our study, after definition of the interest concept and the brief history of its development, relevant theoretical approaches, the principal economic theories, namely the Classical, Neo-Classical, Keynesian Portfolio, and the monetarist economic theories have been dealt with in the subsections in chronological order, and the determination of interest has been discussed under light of such theories. After relevant theoretical approach in Section Two, factors determining the structure of interest rates have been considered in detail. Principally, we have tried to reveal in our thesis, to what extend the freed and raised interest rates as an instrument of an anti-inflationary policy prevent inflation; further, to what extend the credit and stability policies are secured. In doing so, the issue has been dealt with by a theoretical approach and in Section Three of our thesis, we have dealt with The Factors Determining Interest Rates, The Monetary Transfer Mechanisms Required by Monetary Policy Transfer Process with Different Approaches, and the Turkish Practice. After the general assessment of the Interest Policy in developing countries and Turkey in the Turkish Practice relating to our thesis, we have reviewed the development of interest policies implemented since 1980 and 1989 up to today. In Section Five, the interest rate concept is explained in detail and the development of the regulatory and institutional structure for interest rates in Turkey are considered and changes in interest rates in Turkey are revealed. After review of our interest regime, as guided and free interest regime in Section Six, we have tried to analyze the Domestic Savings Rate and Interest Rate, Nominal and Real Interest Rates and the relations between Inflation and Treasury Interest Rates. In Section Eight, the structure, development and determinants of deposits and credits in interest regime periods distinguished as the guided and free interest regimes have been considered. Data for the period discussed in this section relates to the years after 1980 as much as possible. However, data relating to distribution of bank credits by economic sectors, which has been discussed in connection with credits in our thesis, begins from 1870. In the Section of Conclusions, under the light of all theoretical and empirical knowledge, we have tried also to present various proposals after a general arrangement of the Turkish Practice, we have stated our thoughts and prospects, the reason of this is our wish that Turkey has its position in the global world fully, appears as a country that has solved its economic issued in the eve of the European Union and as a universal country holding the capacity of a producing country, not a consumer one. In a globalizing world, as a person passionately fond of Great Turkey, I am in favour of development of strategic policies, not policies despite everything. Because certain processes have been wrongly interpreted by practitioners in Turkey, concession in nature of capitulations have been granted continuously and the present change process has been reached. I would like to quote a sentence of Machiavelli: Don't think that the light at the end of the tunnel is brightness, it might be the headlamp of the train coming onto you. Up to date, we have followed this logic, like firefly flying to light, we have gone to artificial model lights that have almost prepared our fate and lost time continuously. In spite of everything, we are powerful, dynamic, because we are too young so that we can overcome the difficulties. Now it is the right time to change, for a sparkling Turkey in the new millennium: quality in every respect, justice and honesty in every matter, to bring practitioners on power who monitor the technology, treat in justice, develop policies making all individuals constructive and productive, catch with the information era, specialize and work in departments, target to position Turkey at the top of a new world order, and do not target only to save the day. Change is necessary to bring all such positive sentiments into practice. In depends on total democracy, change of major part of political parties code and constitution, realization of economic and social reforms, challenge to bring our education to the level of really developed countries. The noble blood flowing in our vessels will absolutely bring us to our target. In fact, this introductory part was to be included in the section of Conclusions; however, I wanted to point in advance at the economical difficulties in Turkish economy, so that sound evaluations can be made until reaching the Section of Conclusions. I believe you better understand the concept that, the person who has not thought of the fate in advance, returns to the beginning, at the end of the thesis. I think that we do not have time to return to the starting point.
Keywords: Faiz Türkiye